Determinants of stock market return: The case of emerging countries / Mohd Shukri Amre Mohd Arif - Mohd Arif, Mohd Shukri Amre (Faculty of Business Management, 2017)
Macroeconomic variables play an important role in the performance of stock market returns. Numerous studies document that there are link between macroeconomic variables and equity returns. It is found that changes in the macroeconomic environment affect the price of share. Stock market returns and macroeconomic variables, investors might guess how stock market behaved if macroeconomic indicators such as exchange rate, industrial productions, interest rate, and money supply fluctuate. This research will focus on developing or emerging countries on how their stock price been influences by macroeconomics variables. There are five macroeconomics variables uses in this research which are Exchange Rate, Gross Domestic Product (GDP), Inflation Rate, Interest Rate and Money Supply. The findings indicate there are two variables that having positive significant relationship between independent variables and dependent variables. The two variables significantly related to the stock market are Gross Domestic Product (GDP) and Money Supply. The result had been record, interpret and present in this research. The data collected from chosen three (3) of seven (7) emerging countries which are Brazil, China and India. The duration of data taken from the year 2000 until 2015.